2021
DOI: 10.2105/ajph.2021.306509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Government-Implemented Cash Plus Model on Violence Experiences and Perpetration Among Adolescents in Tanzania, 2018‒2019

Abstract: Objectives. To examine the impacts of a government-implemented cash plus program on violence experiences and perpetration among Tanzanian adolescents. Methods. We used data from a cluster randomized controlled trial (n = 130 communities) conducted in the Mbeya and Iringa regions of Tanzania to isolate impacts of the “plus” components of the cash plus intervention. The panel sample comprised 904 adolescents aged 14 to 19 years living in households receiving a government cash transfer. We estimated intent-to-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In line with two existing studies (Bandiera et al 2019;Özler et al 2020), the intervention evaluated here had some protective impacts on sexual behaviors and SRH seeking, increasing health-seeking behavior. Reported elsewhere, the program also reduced experiences of sexual violence and the perpetration of physical violence (Palermo, Prencipe, and Kajula 2021). In line with many studies, however (Austrian and Muthengi 2014;Austrian et al 2016Austrian et al , 2018, the cash plus intervention failed to find impacts on indicators such as contraceptive use, fertility, or a number of sexual partners.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In line with two existing studies (Bandiera et al 2019;Özler et al 2020), the intervention evaluated here had some protective impacts on sexual behaviors and SRH seeking, increasing health-seeking behavior. Reported elsewhere, the program also reduced experiences of sexual violence and the perpetration of physical violence (Palermo, Prencipe, and Kajula 2021). In line with many studies, however (Austrian and Muthengi 2014;Austrian et al 2016Austrian et al , 2018, the cash plus intervention failed to find impacts on indicators such as contraceptive use, fertility, or a number of sexual partners.…”
Section: Discussionmentioning
confidence: 57%
“…2020), the intervention evaluated here had some protective impacts on sexual behaviors and SRH seeking, increasing health‐seeking behavior. Reported elsewhere, the program also reduced experiences of sexual violence and the perpetration of physical violence (Palermo, Prencipe, and Kajula 2021). In line with many studies, however (Austrian and Muthengi 2014; Austrian et al.…”
Section: Discussionmentioning
confidence: 99%
“…We screened 3335 titles and abstracts, removed 2515 (863 were duplicates and 1652 were not relevant), and subsequently assessed 820 full-text articles. Twenty-one studies met the inclusion criteria, and 20 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 provided data for calculating effect sizes (eFigure 1 in the Supplement ). We could not retrieve the necessary data to compute the effect size for 1 study, 44 and this was subsequently excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies (55%) were conducted in North America, 24 , 28 , 29 , 32 , 33 , 34 , 38 , 39 , 40 , 42 , 43 2 (10%) in Europe, 27 , 35 and 7 (35%) in sub-Saharan Africa. 25 , 26 , 30 , 31 , 36 , 37 , 41 The mean age of participants ranged from 11 to 17.6 years old. Fifteen studies (75%) were school-based prevention programs and 5 (25%) were conducted in different settings, such as at a community agency.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pathway indicators examined here do not fully explain the effects on mental health. In work published elsewhere, investigators found that the intervention increased equitable gender attitudes ( 35 ) and reduced experiences of sexual violence and the perpetration of physical violence ( 36 ). These results may have contributed to better mental health, as violence perpetration among males is associated with increased substance use, less gender-equitable attitudes, and posttraumatic stress disorder and depression ( 37 ).…”
Section: Discussionmentioning
confidence: 99%